Efficacy of Sodium-Glucose Transport Protein 2 Inhibitors (SGLT-2) and Dipeptidyl Peptidase 4 (DPP-4) Inhibitor in Weight Reduction in Patients with Type II Diabetes Mellitus - Pansota, Qamar Javaid; Khan, Rizwan Rasul; Majeed, Muhammad Muneeb (Indus Journal of Bioscience Research, 2025)
Objectives: to compare the efficacy of sodium-glucose cotransporter 2 (SGLT-2) inhibitors and dipeptidyl peptidase-4 (DPP-4) inhibitors in achieving weight reduction among patients newly diagnosed with type 2 diabetes mellitus (T2DM). Study Settings Department of Medicine, Aziz Fatimah Hospital, Faisalabad. Duration of Study: This randomized controlled trial was conducted over a period of six months following approval from the Institutional Ethical Review Committee. Data Collection: A total of 60 patients (30 in each group) were enrolled using non-probability consecutive sampling. The SGLT-2 inhibitor group received empagliflozin (10 mg once daily), while the DPP-4 inhibitor group received sitagliptin (50 mg once daily), in addition to their usual diabetic treatment. The primary outcome was achieving ≥3% weight reduction over 12 weeks. Results: The mean weight reduction percentage in the SGLT-2 inhibitor group was 4.72% ± 0.74%, significantly higher than in the DPP-4 inhibitor group (1.78% ± 1.12%, p<0.001). A remarkable higher proportion of patients in the SGLT-2 inhibitor group (88.1%) achieved ≥3% weight loss compared to the DPP-4 inhibitor group (11.9%, p<0.001). Conclusion: Significant efficacy was recorded in SGLT-2 inhibitors while achieving weight reduction in newly diagnosed T2DM patients compared to DPP-4 inhibitors.